Lung tumors: early and delayed ratio of 99mTc-methoxy-2-isobutylisonitrile accumulation - Nikoletić, Katarina; Mihailović, Jasna; Srbovan, Dolores; Kolarov, Violeta; Žeravica, Radmila (Vojnosanitetski pregled, 2014)
Background/Aim. Currently used radiopharmaceuticals are nonspecific and most of them are accumulated by benign tumors as well as inflammatory lesions, abscess or granulomatous lesions. Some factors such as the choice of radiopharmaceutical applied, histopathologic type of tumor, its size, location or previous tumor treatment could influence tumor imaging sensitivity. The aim of this study was to investigate accumulation of 99mTc-methoxy-2-isobutylisonitrile (99mTc-MIBI) by counting early/delayed uptake and release of this radiopharmaceutical inside lung tumors and evaluating possible factors which could be involved in its accumulation. Methods. Two-phase 99mTc-methoxy-2-isobutylisonitrile single photon emission computed tomography scan (early and delayed scan) was performed in 60 patients with lung tumors (the group 1 – 30 benign, and the group 2 – 30 malignant tumors). We calculated the uptake ratio on early (early ratio – ER), delayed images (delayed ratio – DR) and retention index (RI). Individual influence of etiology, diameter, localization, and histological type on uptake/release values was evaluated with regression analysis. Results. The values of ER and DR were significantly different in both groups (p < 0.01), showing lower values in benign vs malignant lung tumors (ER 1.36 ± 0.094 and DR 1.25 ± 0.089 vs ER = 1.93 ± 0.106 and DR = 1.7 ± 0.095 respectively). Tumor size showed a significant influence on the change of ER and DR values (p < 0.01), with greater uptake in tumors > 3 cm. RI values showed no significance between the two groups (p > 0.05). Conclusion. The uptake ratio of 99mTc-methoxy-2-isobutylisonitrile could be a useful index in differentiating lung tumors, while RI has no influence on this. Among the evaluated factors, ER and DR values are significantly influenced only by the diameter of lung tumor, while localization or different histological types between the groups has no influence on this.
Keywords: radiopharmaceuticals; tomography; emission-computed; lung neoplasms; diagnosis; differential; pathology; sensitivity and specificity